2015
DOI: 10.1371/journal.pone.0136646
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Treponema denticola / Prevotella intermedia Co-Infection Are Associated with Severe Periodontitis in a Thai Population

Abstract: Periodontitis is a polymicrobial infection of tooth-supporting tissues. This cross-sectional study aimed to examine the associations between five target species and severe periodontitis in a Thai population. Using the CDC/AAP case definition, individuals diagnosed with no/mild and severe periodontitis were included. Quantitative analyses of Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Tannerella forsythia (Tf), Treponema denticola (Td), and Prevotella intermedia (Pi) in subgingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 34 publications
4
51
0
3
Order By: Relevance
“…We found that P. intermedia exhibited potential similar to that of P. gingivalis and T. denticola to cleave sBL proteins, but that F. nucleatum and A. actinomycetemcomitans do not cleave sBL proteins. These data suggest that degradation of the sBL is not exclusive to late colonizers and are coherent with studies reporting a low presence of A. actinomycetemcomitans in patients with periodontal diseases . Therefore, P. intermedia, a member of the bridging colonizers, could technically act to ‘weaken’ the gingival seal, thereby facilitating infiltration of the more aggressive, late‐colonizing species into the gingiva.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found that P. intermedia exhibited potential similar to that of P. gingivalis and T. denticola to cleave sBL proteins, but that F. nucleatum and A. actinomycetemcomitans do not cleave sBL proteins. These data suggest that degradation of the sBL is not exclusive to late colonizers and are coherent with studies reporting a low presence of A. actinomycetemcomitans in patients with periodontal diseases . Therefore, P. intermedia, a member of the bridging colonizers, could technically act to ‘weaken’ the gingival seal, thereby facilitating infiltration of the more aggressive, late‐colonizing species into the gingiva.…”
Section: Discussionsupporting
confidence: 83%
“…with studies reporting a low presence of A. actinomycetemcomitans in patients with periodontal diseases (30,32). Therefore, P. intermedia, a member of the bridging colonizers, could technically act to 'weaken' the gingival seal, thereby facilitating infiltration of the more aggressive, late-colonizing species into the gingiva.…”
Section: Degradation Of Epithelial Attachmentmentioning
confidence: 99%
“…In aggressive periodontitis (AgP) that affects younger individuals, the facultative anaerobic Gram‐negative bacterium Aggregatibacter actinomycetemcomitans is often detected in high numbers at diseased lesions 1–3 . Longitudinal studies have shown significantly increased risk for attachment loss (AL) in periodontally healthy carriers of A. actinomycetemcomitans compared with individuals without this bacterium 4–6 .…”
mentioning
confidence: 99%
“…Many different species of bacteria have been suggested as the etiological factor of periodontal disease. Nowadays, the following species are considered to be of crucial importance in the initiation and maintenance of periodontitis: Aggregatibacter actinomycetemcomitans ; P. gingivalis ; and Tannerella forsythia . To initiate inflammation, a host defense response against these bacteria is required .…”
Section: Methodsmentioning
confidence: 99%